2009
DOI: 10.1177/0271121408328173
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Consensus on a Definition of Professional Development for the Early Childhood Field

Abstract: Reaching consensus on the meaning of professional development is needed to integrate professional development across various sectors of the early childhood field, distinguish various professional development approaches, match learning opportunities to learner characteristics, and evaluate its effects on professional practices and child and family outcomes. This article proposes a definition and conceptual framework for professional development across all sectors of early childhood and describes methods used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 4 publications
2
106
0
1
Order By: Relevance
“…In their project to define 'professional development' in ECE, Buysse et al (2009) outline the six assumptions that guided their thinking: that it encompasses a wide range of learning opportunities; it serves a diverse workforce; that families are essential partners; that learners must actively engage in learning experiences; that providers should facilitate experiences that respond to problems in practice; and that professional development should be conceptualised via three intersecting components -the who, the what, and the how (p. 238). This article is an attempt to move beyond such basic and instrumental assumptions, to argue instead that professional development in ECE should be understood as multi-vocal, historically and culturally situated, and proceed from bringing to consciousness persistent contradictions in practice.…”
Section: Resultsmentioning
confidence: 99%
“…In their project to define 'professional development' in ECE, Buysse et al (2009) outline the six assumptions that guided their thinking: that it encompasses a wide range of learning opportunities; it serves a diverse workforce; that families are essential partners; that learners must actively engage in learning experiences; that providers should facilitate experiences that respond to problems in practice; and that professional development should be conceptualised via three intersecting components -the who, the what, and the how (p. 238). This article is an attempt to move beyond such basic and instrumental assumptions, to argue instead that professional development in ECE should be understood as multi-vocal, historically and culturally situated, and proceed from bringing to consciousness persistent contradictions in practice.…”
Section: Resultsmentioning
confidence: 99%
“…A key to accomplishing this goal is to assure that the quality of training provided is of the highest caliber, relevant, practical, and immediately applicable to the child care workforce (Barnett 2004). A recommendation by Buysse et al (2009) to have a conceptual framework of professional development that included all categories of individuals working in child care could contribute to a greater sense of professionalism for the child care field. Efforts to ensure positive collegial working relationships, providing training related to managing stress, skill based knowledge concerning balancing job demands and other mental health related issues could all help the child care professional with the demands of the occupation.…”
Section: Discussionmentioning
confidence: 99%
“…When creating universal standards of professional development policymakers should consider the diverse needs of both represented families and the actual institutions providing care (NAEYC 1993;Kagan et al 2008). Professionals can reach their goals using a variety of pathways, including quality training, relevant education, teacher mentoring, and technical classroom assistance within a career lattice (Buysse et al 2009;NPDCI 2008;NAEYC 1993;LeMoine 2008;Whitebook 1997). Jorde-Bloom (1988) reported that, when asked, early childhood educators said they would choose a career in teaching if they had to start their career over again.…”
Section: Introductionmentioning
confidence: 99%
“…For many, professional development in early childhood education has been a reform movement premised upon the ideas of teachers as transforming agents, teachers' accountability, and teachers' professionalism (Buysse, Winton & Rous, 2009;DarlingHammond, 2010). The goals of professional development of early childhood teachers are therefore couched in terms of teachers' responsibilities for making effective changes in improving their professional work with children.…”
Section: Professional Development In Early Childhood Education: a Brimentioning
confidence: 99%
“…It has also been recognized that professional development activities can be time consuming, and limited with resources, support and appropriate approach to evaluation (Battey & Frank, 2008). The focus on teaching skills is also an issue in early childhood teachers' professional development (Buysse et al, 2009). …”
Section: Professional Development In Early Childhood Education: a Brimentioning
confidence: 99%